INVESTIGATION OF THE EFFECT OF NeuROPLAY METHOD ON DEVELOPMENTAL PROCESSES OF CHILDREN WITH AUTISM SPECTRUM DISORDERS AND PARENTAL INTERACTIONS - Ekici, Barış; Bıçakçı, Müdriye Yıldız; Dursun, Sezen Serife; Kutlu, Feyza; Gürkan, Elif Nur (PEOPLE: International Journal of Social Sciences, 2019)
This study was conducted to examine the effect of neuroPLAY on the developmental processes and parental interactions of children with autism spectrum disorder. A mixed method was used in the study. In the quantitative dimension of the study, 41 children with an autism spectrum disorder age 18-42 months, and in the qualitative dimension five children and their parents with autism spectrum disorder were included. The qualitative dimension of the study was used and the observation method was carried out in the institutional environment through individual participant and unattended and video recordings in the home environment. Observation was conducted both to determine the developmental process of the child and the parental interaction and to monitor the process of applying the parent/caregiver’s neuroPLAYy method. In the quantitative dimension, experimental design is used. The experimental training period lasted at least 3 months as neuroPLAY. Prior to the start of the experimental training period, five days of training were given to parents and caregivers, and the experts provided feedback on the parent/caregiver through the process of observation. The results of the research show that neuroPLAY has positive effects on developmental processes and parental interactions of children with autism spectrum disorder.